2021
DOI: 10.3390/jpm11020129
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Patterns in Patients with Parkinson’s Disease: A Systematic Review

Abstract: (1) Background: Cardiovascular autonomic dysfunction is a non-motor feature in Parkinson’s disease with negative impact on functionality and life expectancy, prompting early detection and proper management. We aimed to describe the blood pressure patterns reported in patients with Parkinson’s disease, as measured by 24-h ambulatory blood pressure monitoring. (2) Methods: We conducted a systematic search on the PubMed database. Studies enrolling patients with Parkinson’s disease undergoing 24-h ambulatory blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 53 publications
1
6
1
3
Order By: Relevance
“…In subgroup analysis, SBP and PP were significantly higher in the ARP group than in the TDP group. e ARP subtype may be more prone to cardiovascular disease than the TDP subtype, and this finding is in accordance with several other studies [21][22][23]. However, this issue is controversial, and there are a few reports on TDP subtypes with more severe impairment of the cardiac sympathetic system than the ARP subtypes; this was later negated in a slightly larger study by the same authors [24,25].…”
Section: Discussionsupporting
confidence: 88%
“…In subgroup analysis, SBP and PP were significantly higher in the ARP group than in the TDP group. e ARP subtype may be more prone to cardiovascular disease than the TDP subtype, and this finding is in accordance with several other studies [21][22][23]. However, this issue is controversial, and there are a few reports on TDP subtypes with more severe impairment of the cardiac sympathetic system than the ARP subtypes; this was later negated in a slightly larger study by the same authors [24,25].…”
Section: Discussionsupporting
confidence: 88%
“…This may prone the patient with night-time high blood pressure uncovered therapeutically. 99,140 Other PD therapy, such as L-Dopa, dopamine agonist, or monoamine oxidase inhibitors, may also affect BP fluctuations. [149][150][151][152][153][154] It is suggested that some options such as levodopa sustained-release tablets, dopamine receptor agonists, continuous infusions of levodopa or dopamine agonists by intra-duodenal administration, or deep brain stimulation may avoid BP fluctuations.…”
Section: Management Of Hypertension In Neurodegenerative Diseasementioning
confidence: 99%
“… 111 , 138 , 139 BP measurements must be cautious in PD patients, which might lead to wrong assumptions since the patients are susceptible to dysautonomia manifestations such as orthostatic hypotension, postprandial hypotension, or supine hypertension. 140 The BP decline preceding the onset of mild cognitive impairment and dementia may also lead to wrong assumptions; thus, it states the importance of comprehending the pathophysiology behind the issue. 36 , 123 , 124 As awareness and control are poor in most Asian countries/regions, the highlight must be put on educating about the importance of keeping normal blood pressure and reducing other risk factors related to it, such as reducing obesity and salt intake.…”
Section: Management Of Hypertension In Neurodegenerative Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…[20] Of note, the reverse effect, patients functioning worse in the morning, may be observed in patients suffering from supine hypertension combined with orthostatic hypotension, a combination often seen as part of autonomic dysfunction in advanced Parkinson's disease. [21] The troughs in blood pressure resulting from orthostatic hypotension are typically most pronounced in the morning, not too long after rising from the bed.…”
Section: Dear Sirsmentioning
confidence: 99%